PELAKSANAAN STANDAR OPERASIONAL PROSEDUR (SOP) POLA ASUH PADA ANAK BALITA DI PANTI ASUHAN KASIH SAYANG KOTA BENGKULU - Putri Darmalena; Rufran Zulkarnain; Sofino Sofino (Jurnal Pendidikan Sepanjang Hayat, 2021)
The purpose of this study was to find out and describe in detail the SOP for children under five at the Kasih Sayang Orphanage, Bengkulu City. This research is a descriptive qualitative research. This study uses interview data collection techniques, observation and documentation. The research subjects were Merlin Darlia as the orphanage educator, Riko Tampati as the head of the orphanage and Fera Isnata as the supervisor. Checking the validity of the data used time triangulation, subject triangulation and technical triangulation. The results obtained were the implementation of standard operating procedures for intake of children under five, refreshing activities, sleep schedules, learning activities and prayer schedules. This orphanage has 45 foster children consisting of 7 toddlers 3 babies and 35 teenagers.